2016
DOI: 10.1016/j.bulsci.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

On the rationality of Nagaraj–Seshadri moduli space

Abstract: ABSTRACT. We show that each of the irreducible components of moduli of rank 2 torsionfree sheaves with odd Euler characteristic over a reducible nodal curve is rational.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, it has been shown that the irreducible components M 12 and M 21 of Mξ are rational varieties (cf. ). In particular, they are unirational and hence by a result of Serre they are simply connected.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it has been shown that the irreducible components M 12 and M 21 of Mξ are rational varieties (cf. ). In particular, they are unirational and hence by a result of Serre they are simply connected.…”
Section: Introductionmentioning
confidence: 97%
“…This is needed for computing the limit mixed Hodge structure using Steenbrink spectral sequences. In recent years several authors have studied the algebraic and geometric properties of the Gieseker's moduli space (see for example [5,6,11]). We believe that Theorem 1.1 holds for any number of nodes.…”
Section: Introductionmentioning
confidence: 99%